Islamic civilization in thirty lives : the first 1,000 years - Robinson, Chase F. ([United Kingdom] : Thames & Hudson, 2016)
Religious thinkers, political leaders, lawmakers, writers, and philosophers have shaped the 1,400-year-long development of the world's second-largest religion. But who were these people? What do we know of their lives and the ways in which they influenced their societies? In Islamic Civilization in Thirty Lives, the distinguished historian of Islam Chase F. Robinson draws on the long tradition in Muslim scholarship of commemorating in writing the biographies of notable figures, but he weaves these ambitious lives together to create a rich narrative of Islamic civilization, from the Prophet Muhammad in the seventh century to the era of the world conquerer Timur and the Ottoman Sultan Mehmed II in the fifteenth. Beginning in Islam's heartland, Mecca, and ranging from North Africa and Iberia in the west to Central and East Asia, Robinson not only traces the rise and fall of Islamic states through the biographies of political and military leaders who worked to secure peace or expand their power, but also discusses those who developed Islamic law, scientific thought, and literature. What emerges is a fascinating portrait of rich and diverse Islamic societies.
Part 1. Islam & empire 600-850 : Muhammad, the prophet (632) --'Ali: cousin, caliph and forefather of Shi'ism (661) --'A'isha: wife of the Prophet (678) --'Abd al-Malik: engineer of the caliphate (705) -- Ibn al-Muqaffa': translator and essayist (759) -- Rabi'a al-'Adawiyya: renunciant and saint (801) -- al-Ma'mun: caliph-patron (833) -- Part 2. The Islamic commonwealth 860-1050 :'Arib: courtesan of caliphs (890) -- al-Hallaj:'the Truth' (922) -- al-Tabari: traditionalist rationalist (923) -- Abu Bakr al-Razi: free-thinking physician (925 or 935) -- Ibn Fadlan: intrepid envoy (fl. tenth century) -- Ibn Muqla: vizier, scribe, calligrapher? (940) -- Mahmud of Ghazna: conqueror and patron (1030) -- al-Biruni: cataloguer of nature and culture (c. 1050) -- Part 3. A provisional synthesis 1050-1250 : Ibn Hazm: polemicist, polymath (1064) -- Karima al-Marwaziyya: hadith scholar (1070) -- al-Ghazali:'Renewer' of Islam (1111) -- Abu al-Qasim Ramisht: merchant millionaire (c. 1150) -- al-Idrisi: cosmopolitan cartographer (1165) -- Saladin: anti-Crusader hero (1193) -- Ibn Rushd (Averroes): Aristotelian monotheist (1198) -- Part 4. Disruption & integration 1250-1525 : Rumi: Sufi'poet' (1273) -- Rashid al-Din: physician, courtier and global historian (1318) -- al-Hilli: paragon of Shi'ism ascendant (1325) -- Ibn Taymiyya: stubborn reactionary (1328) -- Timur: sheep-rustler, world-conqueror (1405) -- Ibn Khaldun: social theorist and historian (1406) -- Mehmed II: conqueror and renaissance man (1481) -- Shah Isma'il: esoteric charismatic (1524).
Includes bibliographical references (pages 248-266) and index.
Sumbangan Mohamad Taha (2017).
Keywords: Islamic civilization; Middle East -- Biography